σ-Ideals in distributive pseudocomplemented residuated lattices - Celani, Sergio Arturo (2015)
In this paper we shall introduce the notion of σ- ideals in the variety of pseudocomplemented residuated lattices.We shall also give some characterizations of the stonean pseudocomplemented residuated lattices.